Facile Synthesis of Spirocyclic Tetrahydroquinolines via C(sp3)–H Functionalization in a Cascade Redox Process - Yu, Liping; Qiu, Bin; Dong, Peizhen; Xiao, Jian; Yu, Shitao (Synthesis, 2021)
An environmentally benign cascade redox process was developed for the efficient construction of the pharmaceutically significant spirocyclic tetrahydroquinolines via sequential SNAr/Knoevenagel condensation/[1,5]-hydride transfer/cyclization. This green transformation has the features of being catalyst-free, additive-free, operationally simple, and has high step- and atom-economy.
Keywords: tetrahydroquinoline; C–H functionalization; cascade reaction; hydride transfer